Effect of Polymorphism of some Candidate Genes from Growth Hormone Axis on Egg Production Traits in Mazandaran Native Fowls - B Enayati; Gh Rahimi Mianji (پژوهشهای علوم دامی ایران, 2012)
In the present study the allelic polymorphisms of GH, GHR and TGFβ3 genes and its association with egg production traits were investigated. Blood samples randomly were collected from breeder hens of Mazandaran native fowls breeding station and transported to the laboratory in cold chain condition. DNA was extracted using modified salting out method and the desired loci were amplified by specific primers. All samples genotyping were carried out by RFLP-PCR method. The frequency of each (+) and (-) alleles was estimated at 0.7981 and 0.2019 for GH, 0.9937 and 0.0063 for GHR and 0.8037 and 0.1961 for TGFβ3 loci, respectively. The heterozygote genotype was detected in both GH and TGFβ3 loci but all individuals showed homozygote genotype in GHR marker site. The chi-squared test showed that all individuals in both GH and TGFβ3 loci were in HW equilibrium. Statistical analysis of showed that GH marker site had a significant effect on both phenotypic and breeding values of egg weight at puberty (EWM) and age at first laying egg (AFE), respectively. The mean comparison showed that individuals with -/- genotype in GH marker site had higher phenotypic values for EWM but lower breeding values for AFE trait. The GHR and TGFβ3 loci and also the interaction between GH×TGFβ3 loci were not statistically significant on phenotypic and breeding values of mentioned traits..